2015
DOI: 10.1038/ismej.2015.49
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Culture and molecular-based profiles show shifts in bacterial communities of the upper respiratory tract that occur with age

Abstract: After the publication of this paper, an error was noticed in the sentences 'Phylogenetic analysis using the 16S-23S rRNA internal transcribed spacer region revealed that the AMZ-associated Prochlorococcus assemblages are mainly composed of two novel LL ecotypes (termed LL-V and LL-VI), which correspond to basal groups linking Prochlorococcus with marine Synechococcus (Lavin et al., 2010), the other dominant marine picocyanobacteria. However, no genomic or picocyanobacterium information exists for these AMZ lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The paired-end Illumina 16S rRNA community profiling of bacteria has been successfully applied to human clinical samples to provide a more robust evaluation of polymicrobial infections [ 47 , 55 57 ]. To our knowledge, this was the first study in which paired-end Illumina 16S rRNA gene community profiling was done on whole blood.…”
Section: Discussionmentioning
confidence: 99%
“…The paired-end Illumina 16S rRNA community profiling of bacteria has been successfully applied to human clinical samples to provide a more robust evaluation of polymicrobial infections [ 47 , 55 57 ]. To our knowledge, this was the first study in which paired-end Illumina 16S rRNA gene community profiling was done on whole blood.…”
Section: Discussionmentioning
confidence: 99%
“…In the nasopharynx, which is also lined with pseudostratified ciliated epithelium originating from the fetal endoderm, the community composition becomes more complex, although aerobic and facultative anaerobic genera like Moraxella, Staphylococcus, Corynebacterium, Dolosigranulum, Hemophilus, and/or Streptococcus spp. still predominate (28,344,352). Although generally found in low abundance, oral bacteria are common in this niche as well.…”
Section: A Development Of Stable Microbial Ecosystems In the Airwaymentioning
confidence: 99%
“…This process is dynamic and continues throughout infancy, resulting from exposure to new environmental factors including those that occur as a result of respiration and feeding. Ultimately, increasingly complex and niche-specific communities emerge (42,344). Natural selection for the microorganisms best fitted to these niches continues throughout life as the host encounters new environments and changes in diet, becomes a member of larger and different communities (e.g., day care, schools, military institutes, nursing homes), and experiences life events that alter the host's response to the environment (27)(28)(29)305).…”
Section: A Development Of Stable Microbial Ecosystems In the Airwaymentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional study of children and adults ( n = 51 children, aged 1–4.5 years; n = 19 adults) in Canada demonstrated that, like the gastrointestinal microbiota [ 4 ], changes in NP bacterial microbiota occur with increasing age; less diverse communities are observed in younger children and more even, diverse communities are characteristic of adults [ 5 ]. The beta-diversity of bacterial communities was more similar in adults compared to that observed in children, indicating greater heterogeneity in upper airway microbiota in early life [ 5 ]. Teo et al also recently demonstrated, using longitudinally obtained NP samples collected over the first year of life from a cohort of 234 Australian infants, that the NP microbiota undergoes compositional development during this period [ 6 ].…”
Section: Introductionmentioning
confidence: 99%